Budikdamber akuaponik sebagai strategi ketahanan pangan dan stimulus kewirausahaan saat pandemi covid-19 - Helin G Yudawisastra; Wasifah Hanim; Siti Mardiana; Alfiana; Sugiartiningsih; Suparjiman; Tris Sudarto; Eris Sudarisman; H. Qur’ani Noor (LPPMPK-Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
During the Covid-19 pandemic, this civic duty project aims to increase community food security, particularly for the orphanage community. Given that the pandemic had been active for 2 (two) years and had an adverse effect on the local economy, this activity was conducted. The training exercise that was conducted involved training for fish growing in buckets (budikdamber). Additionally, food safety, Due to the fact that the outcomes of budikdamber can be sold, it can also be used as an entrepreneurial teaching tool. The Insan Harapan Child Orphanage (PSAA), located in Jl. Ahmad Yani no. 37/132 Gang Slamet II, Babakan Surabaya, Kiaracondong, Bandung 40281, hosted the events. Catfish, kale seedlings, special plastic buckets for cultivation, and a few plastic cups make up the ingredients and equipment. The orphanage's residents and managers are the subject of this research method's descriptive analysis. One day of instruction is followed by a few weeks of evaluation. It is anticipated that training outcomes will be put to good use for personal consumption and have a favorable impact on the economy both during and after the pandemic. The children and teenage residents as well as the administrators of the orphanage now have information and abilities that are highly helpful. It is hoped that aquaponics farming will endure and develop in the future.